Influence of the aerial burrknot galls on the initial development of the apple plants - Chrun, Antonio Sergio; Fachinello, José Carlos; Rossetto, Edemar Antonio (Pesquisa Agropecuaria Brasileira, 1992)
Aerial burrknot type galls, which are common in apple rootstocks, cause partial brake of the vascular tissue of plants, reducing the production. With the objective of evaluating the injury those tumors on the initial development of the plants, caused by this experiment was carried out from June 1988 to July 1990, at the Universidade Federal de Pelotas. An orchard with 84 apple stock plants at the cultivar Fuji and Gala on rootstock MM-106. The following treatments were used: a) stocks with galls; b) stocks with the galls removed; c) stocks with no galls. The evaluation of the plants was made through the vigor measuring the diameter of the stem, at different heights and different periods of time. From the results it is possible to say that the presence of galls on rootstocks modify the initial development of apple plants and that stocks planted with no galls, had a better vigor. Remotion of galls can cause stress on plants and development delay.